Curie point Depth and Heat Flow Analyses over Part of Bida Basin, North Central Nigeria using Aeromagnetic Data - Adewumi, Taiwo; Salako, Kazeem Adeyinka; Adediran, Sunday Obadare; Okwokwo, Oke Israel; Sanusi, Yusuf A (Journal of Earth Energy Engineering, 2019)
This study attempt to estimate the Curie point depth and heat flow using high resolution aeromagnetic data over part of Bida basin bounded with longitude 5o00’E – 6o30’E and Latitude 8o30’N – 9o30’N with an estimated total area of 18,150 km2. We subjected the total magnetic intensity field of the study area to regional/residual separation using polynomial fitting. We divided the residual map into sixteen overlapping spectral blocks. We obtained centroid depths and depth to top of basement got from the plot of log of power spectrum against wave number; the centroid depth ranges from 6.61 km to 20.30 km while the depth to top of basement ranges from 1.59 km to 6.38 km. input parameter to calculate the curie depth. The CPD range from 10.88 km to 35.51 km with an average value of 23.22km. The CPD is deeper at the centre of the southern and eastern part of the study area which correspond to part of Pategi and part of Baro; and shallow at the northeastern and Northwestern part of the study area correspond to part of Mokwa and part of Bida. The geothermal gradients for the sixteen blocks range from 16.33 oCkm-1 at the centre of the southern region of the area to 53.30 oCkm-1 at the northeastern and north western region of the study area with an average of 28.98 oCkm-1. While the heat flow to range from 40.99 mWm-1 to 133.80 mWm-1 with an average value of 76.19 mWm-2. It can be deduced from this study that the Southeastern, southwestern, and the northwestern part of the study area might be a good indicator of geothermal energy potential with minimum CPD, maximum geothermal gradient and heat flow since demagnetized rocks confirm a hot rock quantity in the crust that can be harnessed for geothermal energy exploitation.